The challenges of sustained development : the role of socio-cultural factors in East-Central Europe - Adam, Frane (Central European University Press, 2005)
How wide is the gap between the new democracies of East-Central Europe and the most developed European nations? How can it be narrowed? The book is trying to address these issues in a comprehensive way, taking into account not only economical but socio-cultural and political aspects of development.
Keywords: Europe, Central -- Social conditions -- 1989-; Europe, Eastern -- Social conditions -- 1989-; Social change -- Europe, Central.; Social change -- Europe, Eastern.; Sustainable development -- Europe, Central.; Sustainable development -- Europe, Eastern.; Europe, Central -- Economic conditions -- 1989-; Europe, Eastern -- Economic conditions -- 1989-; Social indicators -- Europe, Central.; Social indicators -- Europe, Eastern.; Changement social -- Europe de l'Est.; Changement social -- Europe centrale.; Développement durable -- Europe centrale.; Développement durable -- Europe de l'Est.; Indicateurs sociaux -- Europe centrale.; Indicateurs sociaux -- Europe de l'Est.; Europe centrale -- Conditions sociales -- 1989-; Europe de l'Est -- Conditions sociales -- 1989-; Europe centrale -- Conditions économiques -- 1989-; Europe de l'Est -- Conditions économiques -- 1989-; SOCIAL SCIENCE -- Regional Studies.; SOCIAL SCIENCE -- Anthropology -- General.; SOCIAL SCIENCE -- Sociology -- General.; Economic history; Social change; Social conditions; Social indicators; Sustainable development; Central Europe; Eastern Europe; Since 1989